An Accidental Synthetic Chemist - Collum, David B. (Synthesis, 2025)
A journey is described that began as a genetics major, passed through a brief period as a formal synthetic organic chemist, and proceeded through a decades-long quest to be a physical organic–organometallic chemist. Although a preponderance of our program has emphasized elucidating fundamental principles of how aggregation and solvation influence reactivity, this review focuses on the results that have implications in organic synthesis.
Keywords: aggregation; asymmetric synthesis; carbanions; enantioselectivity; lithiation; solvent effects; stereoselective synthesis; organometallic reagents